How and When Workplace Incivility Undermines Job Embeddedness: the Roles of Job Satisfaction and Protean Careers in Gen Z - Hendryadi Hendryadi; Dinda Puri Melani; Faris Faruqi (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: In today's dynamic work environments, understanding the factors that influence employee retention is crucial. For Generation Z, the newest cohort in the workforce, negative interpersonal experiences, such as workplace incivility, pose a significant threat to their stability and integration within an organization.Purpose: This study advances job embeddedness theory by examining workplace incivility as an antecedent while investigating the mediating mechanism (job satisfaction) and boundary condition (protean career attitudes) that explain and modify this relationship.Design/methodology/approach: Data were collected from 382 Generation Z employees across various Indonesian industries using a two-wave time-lagged design. Hypotheses were tested using PROCESS analysis in SmartPLS 4.0, incorporating moderated mediation to examine the proposed relationships.Findings/Results: This study revealed that workplace incivility negatively impacts both job satisfaction and job embeddedness, with job satisfaction mediating the incivility-embeddedness relationship. Protean career attitudes (PCA) moderated these relationships by (1) buffering the adverse effects of incivility on job satisfaction and embeddedness and (2) amplifying the positive relationship between satisfaction and embeddedness, with effects strengthening at higher PCA levels.Conclusion: This study confirms that workplace incivility reduces job embeddedness by lowering job satisfaction among Gen Z employees. However, protean career attitude (PCA) acts as a key resilience factor, buffering this negative effect. It weakens the impact of incivility on satisfaction. Originality/value (State of the art): This study makes dual theoretical contributions by (1) identifying job satisfaction as the psychological mechanism translating incivility into reduced embeddedness and (2) demonstrating PCA's novel dual function as both a buffer against adverse effects and amplifier of positive relationships in the incivility-embeddedness nexus, particularly for younger generational cohorts. Keywords: workplace incivility; job embeddedness; job satisfaction; protean career attitudes, Gen Z